IFRS Adoption Research in Indonesia: A Systematic Literature Review - Sukmawati Sukmawati; Sri Pujiningsih (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study aimed to review the development of IFRS research literature in Indonesia from 2011 to 2020.Design/Methodology/Approach: This study was based on the IFRS research articles from nationally accredited journals. The method in this research was a systematic literature review with a bibliometric approach and content analysis.Research findings: The results showed that the publication of the IFRS articles increased in 2014 with the number of authors dominated by two researchers. The research in Indonesia was dominated by the theme of the effect of IFRS convergence on earnings quality. Thus, it is necessary to develop research on the theme of implementation and development of IFRS convergence since the articles related to this theme are still poor. Compared with existing research abroad, there was a common focus of research on the theme of the IFRS convergence effect. However, there were differences in research theme trends, where the most studied theme in Indonesia was related to the effect of IFRS convergence, while abroad, the most studied theme was related to the implementation of IFRS convergence.Theoretical contribution/originality: This research can provide a historical overview of the development of the IFRS research literature in Indonesia.Research limitation/Implication: Further research is expected to expand the data analysis and sources of data. The research is also expected to expand the sub-themes related to the implementation and development of IFRS convergence, where the theme had not been studied much yet from 2011 to 2020.